Zambia : Staff Report for The 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that in the last two years, the Zambian economy has been weighed down by large fiscal imbalances, lower copper prices, and policy uncertainties. Real GDP growth has slowed, the current account has deteriorated, international reserves have fallen, and the exchange rate has been under downward pressure. The IMF staff estimates that real GDP growth slowed from 6.7 percent in 2013 to 5.6 percent in 2014, driven by a contraction in copper production. Growth is projected to average 5.5-7 percent a year over the medium term, reflecting the impact of investments in mining and electricity in recent years.